The Study of Emerging Electrical Machine Technologies and Their Applications - Wang, Rong-Jie; Kamper, Maarten J. (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint presents a collection of papers showcasing the latest advancements and research work in the field of electrical machines. The reprint focuses on pioneering electrical machine technologies that have the potential to emerge as the next generation of electrical machines, and their potential applications in various industries. The papers delve into distinct machine technologies, such as flux-intensifying memory machines, Vernier machines, flux-reversal machines, wound rotor machines, line start motors, and doubly fed machines, and explore their applications in areas including electric transportation and renewable energy power generation. The reprint serves as a useful resource for researchers, engineers, and students who are interested in emerging electrical machine technologies.